The question about material composition as a question about boundaries - Núñez Erices, Gonzalo Germán (Estudios de Filosofía, 2019)
Since Peter van Inwagen in his book Material Beings (1990) raised The Special Composition Question, many lines have been written about the conditions for two or more material objects to compose a further object. This paper proposes a study of the relationship between composition and the notion of boundary. The question about composition entails drawing a boundary to determine when it occurs and when it does not. There are three traditional answers: restrictivism, universalism, and nihilism. While according to restrictivism, composition occurs occasionally, according to universalism and nihilism, it occurs either always or never respectively. Nonetheless, despite the opposition of these two answers, both have a common target: to avoid the existence of ontologically vague boundaries for material composition. Thus, how a boundary is drawn will determinewhat kind of things we accept as components of the world.